Acute Heart Failure and Atrial Fibrillation: Insights From the Acute Study of Clinical Effectiveness of Nesiritide in Decompensated Heart Failure (ASCEND‐HF) Trial. Issue 8 (24th August 2015) - Abualnaja, Seraj; Podder, Mohua; Hernandez, Adrian F.; McMurray, John J. V.; Starling, Randall C.; O'Connor, Christopher M.; Califf, Robert M.; Armstrong, Paul W.; Ezekowitz, Justin A.
Abstract : Background: Patients with acute heart failure (AHF) frequently have atrial fibrillation (AF), but how this affects patient‐reported outcomes has not been well characterized. Methods and Results: We examined dyspnea improvement and clinical outcomes in 7007 patients in the Acute Study of Clinical Effectiveness of Nesiritide in Decompensated Heart Failure (ASCEND‐HF) trial. At baseline, 2677 (38.2%) patients had current or a history of AF and 4330 (61.8%) did not. Patients with a history of AF were older than those without (72 vs. 63 years) and had more comorbidities and a higher median left ventricular ejection fraction (31% vs. 27%, P <0.001). Compared to those without AF, patients with AF had a similar mean ventricular rate on admission (81 vs. 83 beats per minute [bpm]; P =0.138) but a lower rate at discharge (75 vs. 78 bpm; P <0.001). There was no difference in dyspnea improvement between patients with and without AF at 6 hours ( P =0.087), but patients with AF had less dyspnea improvement at 24 hours ( P <0.001). Compared to patients without AF, patients with AF had a higher 30‐day all‐cause mortality rate (4.7% vs. 3.3%; P =0.005), a higher 30‐day HF rehospitalisation rate (7.2% vs. 5.3%; P =0.001), and a higher coprimary composite outcome of 30‐day death or readmission (11.6% vs. 8.6%; P <0.001). This difference persisted after adjustment for prognostic variables (adjusted odds ratio=1.19; (95% confidence interval, 1.02 to 1.38; P =0.029). Conclusions: Among patients admitted to the hospital with AHF, current or a history of AF is associated with less dyspnea improvement and higher morbidity and mortality at 30‐days, compared to those not in AF. Clinical Trial Registration: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00475852.